Multiletramentos na formação de professoras(es) de línguas : caminhos para a educação linguística crítica - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This research contemplates relevant approaches that permeate the universe of teacher training for language teachers under the bias of multiliteracies and the perspective of linguistic education, theories that contemplate the social universe referenced in the various linguistic social practices, dialogues with the relationship between technology and training teacher in the graduation of a language course reflecting the need for modernization and reframing to improve the linguistic process amid the processes of modernity and technological advancement. Understanding that contemporaneity encompasses important aspects related to the subjects' life experiences in society, I consider digital technologies as something present in people's way of life and, therefore, it is important in the scenario of teacher education. From this scenario, new forms of language emerge, new forms of reading and writing, new angles to see / in the world. Thus, this research, from the perspective of language education (MATTOS, 2018; DUBOC, 2018), has as its theme the multiliteracies in teacher training, since one of my concerns has been thinking about how to train language teachers for the context current in which the language expands in virtual environments, considering mainly the intercultural elements that constitute us (CANCLINI, 2013). Based on this problem, the objective of the research is to investigate and analyze the perceptions of language teachers about the practices of multiliteracies during the initial training. This discussion was based on studies by Rojo (2012), Jordão (2007), Monte Mór (2007; 2010; 2019), Street (2012; 2014), Barton and Lee (2015), Freitas (2019), Menezes de Souza (2011), among others. For this, developed a research with a qualitative interpretative approach, with the students of the UEG course of Letters, in Inhumas, Goiás. At the end of the research, I present my view on the perception of teachers in formation about the technologies as new forms of language, emerging from the various groups that share our knowledge, as a way to motivate and support new studies, practices and policies for language education in these times.
Multiliteracies in the training of language teachers : paths to critical linguistic education
Keywords: Multiletramentos; Formação de Professoras(es) de línguas; Plataformas digitais; Experiência; Percepção; Multiliteracies; Teacher training; Digital platforms; Experience; Perception; LINGUISTICA, LETRAS E ARTES